A visual tool for generating digital calibration certificates (DCCs) in Excel. (December 2021) - Röske, Dirk
Abstract: Many calibration laboratories use Microsoft Excel for reading and collecting data from measuring instruments. It is also used for calculating calibration results, including measurement uncertainties, according to established procedures and for printing certificates or saving them to files such as PDFs. Much programming effort is usually needed to generate a validated, machine-readable digital calibration certificate (DCC). In this paper, a method is proposed for visually creating a digital certificate using the two schema definitions of dcc.xsd and SI_Format.xsd from PTB if the calibration data is available in Excel. The user does not need to have any programming skills to apply this tool, but a good understanding of the schema definitions is essential.